Antecedents and Performance Consequences of High-Potential Scheme Use - Krebs, Benjamin (Academy of Management Proceedings)

Kunststofftechnik Paderborn: Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen von Thermoplasten - Arndt, Theresa; Schöppner, Volker (Joining Plastics)

Wenn Regeln Potenziale freisetzen - Arndt, Theresa; Schöppner, Volker (K-Zeitung)

Quasi-Simultaneous Laser Transmission Welding - Arndt, Theresa; Schöppner, Volker (PhotonicsViews)

Modellierung des Wärmetransports in zyklisch durchströmten Wärmeübertragern - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppe „Energieverfahrenstechnik“)

Influence of Material Degradation on Weld Seam Quality in Hot Gas Welding of Polyamides - Schöppner, Volker; Bialaschik, Max (73th Annual Assembly of the International Institute of Welding (IIW))

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Interdiffusion in aluminum-steel clad strip - Krivská, Barbora; Šlapáková, Michaela; Kihoulou, Martin; Králík, Rostislav; Bajtošová, Lucia; Cieslar, Miroslav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Proc. 20th Conference of Czech and Slovak Physicists)

Device for twin-roll casting of strips with profiled cross-section - Bondarenko, Serhii; Grydin, Olexandr; Oginskiy, Yosyp; Kuzmina, Olga; Frolov, Yaroslav (Theory and practice of metallurgy)
Goal. This article is devoted to the development of a new method of roll-crystallizers profiling for twin-roll casting in order to provide the possibility of manufacturing strips with variable geometry on width as one of the more widely used products in the world. Method. The proposed method of profiling is implemented by using profiling strips that cover one or both rolls-crystallizers. In this way achieved profiling of the surface of the cylindrical internally water-cooled rolls, which corresponds to the desired type of strips profiled cross-section. Research results. For the practical implementation of the proposed profiling method was developed device for twin-roll of strips with profiled cross- section. In this paper presented the basic scheme of developed device for twin-roll casting of strips with profiled cross-section using endless strips and given the principle of operation of developed device for profiling. Scientific novelty. A feature of the developed device is its universality, which provides the possibility of synchronous rotation of tension, profiled and compensating-tension rollers in perpendicular plane to the axis of rotation of the rolls-crystallizers. This implementation of the device for twin-roll casting allows to manufacture different types of strips with profiled cross-section. Practical significance. For developed device for twin-roll casting of strips with profiled cross-section has been obtained patent for the invention of Ukraine. For further practical implementation of the developed device, considering the adjustments that provide practical implementation on a specific laboratory twin-roll casting unit, the device of twin-roll casting of strips with profiled cross-section was designed. In the work are presented the basic structural elements and their appearance in the form of three-dimensional models.

Aluminum-steel clad material prepared by twin-roll casting - KŘIVSKÁ, Barbora; ŠLAPÁKOVÁ, Michaela; Grydin, Olexandr; CIESLAR, Miroslav (METAL 2020 Conference Proeedings)